2015
DOI: 10.4028/www.scientific.net/amm.797.96
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Analysis of Notched Foam Concrete Beam

Abstract: Nowadays, lightweight foamed concrete (LFC) is increasingly being used for structural purposes. Physical and mechanical properties of LFC are unlike the properties of traditional concrete thus constitutive models for concrete may not be used directly to describe its the fracture behavior. The paper presents an attempt to adapt the elastoplastic model with degradation known as Barcelona model for this purpose. The constitutive model is traditionally used for non-linear analyses of concrete and masonry structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…e tests were carried out on specimens without y ash. Figure 7 includes also the results of experiments carried out by authors and reported in [23][24][25][26][27][28]. e decrease of Advances in Materials Science and Engineeringexural tensile strength with the decrease of the density of the foamed concrete can be noted.…”
Section: Modulus Of Elasticitymentioning
confidence: 95%
See 1 more Smart Citation
“…e tests were carried out on specimens without y ash. Figure 7 includes also the results of experiments carried out by authors and reported in [23][24][25][26][27][28]. e decrease of Advances in Materials Science and Engineeringexural tensile strength with the decrease of the density of the foamed concrete can be noted.…”
Section: Modulus Of Elasticitymentioning
confidence: 95%
“…is is mainly due to the insufficient knowledge regarding its mechanical properties and small number of research on its fracture behaviour [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…As reported in Table 3, the constant w eff /c ratio was fixed equal to 0.44 for all specimens, where w eff is water content, which includes tap water and liquid foaming agent; c is the cement content. This was based on the results of Jones and McCarthy [26], Xianjun et al [76] and the authors' earlier experiments [77][78][79].…”
Section: Compositionmentioning
confidence: 99%
“…Z uwagi na naprężenia rozciągające w spodzie warstwy oraz możliwość ewentualnego pękania [17,21,22], testy takie, chcąc zastosować nowy materiał w konstrukcji nawierzchni, wydają się być szczególnie zasadne.…”
Section: Charakterystyka Materiałowa Pianobetonuunclassified